1993
DOI: 10.1161/01.atv.13.5.702
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate and LDL metabolic heterogeneity in hypercholesterolemia.

Abstract: Metabolic heterogeneity in low density lipoprotein (LDL) may be detected by examination of the daily urinary excretion rate of radioactivity after injection of trace-labeled lipoprotein. Two distinct pools are observed within LDL. The first (pool A) is cleared rapidly from the plasma, whereas the second (pool B) is catabolized more slowly. In the present study we examined LDL metabolism in seven hypercholesterolemic subjects (six women and one man) before and during fenofibrate therapy. Comparison with normoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 40 publications
7
40
0
2
Order By: Relevance
“…The mechanism for increased catabolism of all apoBcontaining lipoproteins with fenofibrate was probably chiefly due to hepatic activation of PPAR-␣ (19). Increased expression of lipoprotein lipase (23) and decreased hepatic apoCIII synthesis (27) could partly explain the increase in FCR of VLDL apoB and IDL apoB, respectively, as well as the increased production of LDL apoB (42,43). The fall in plasma lathosterol agrees with work showing that fibrates suppress cholesterol biosynthesis by inhibiting HMGCoA reductase (47).…”
Section: Regulation Of Apoai and Apob-100 Kineticssupporting
confidence: 77%
See 1 more Smart Citation
“…The mechanism for increased catabolism of all apoBcontaining lipoproteins with fenofibrate was probably chiefly due to hepatic activation of PPAR-␣ (19). Increased expression of lipoprotein lipase (23) and decreased hepatic apoCIII synthesis (27) could partly explain the increase in FCR of VLDL apoB and IDL apoB, respectively, as well as the increased production of LDL apoB (42,43). The fall in plasma lathosterol agrees with work showing that fibrates suppress cholesterol biosynthesis by inhibiting HMGCoA reductase (47).…”
Section: Regulation Of Apoai and Apob-100 Kineticssupporting
confidence: 77%
“…In volunteers with comparable characteris- tics to our population, bezafibrate increased the production and catabolism of LDL apoB (42). The same group later showed that fenofibrate increases the catabolism of VLDL 1 , reducing its conversion of VLDL 2, and also accelerates the production and catabolism of LDL 2 , consistent with a distribution of LDL particles to a larger less dense type (43). Fibrates have also been demonstrated to increase the synthesis of apoAI in familial hyperlipidemias (44,45), but not all reports have been consistent.…”
Section: Regulation Of Apoai and Apob-100 Kineticssupporting
confidence: 73%
“…This enzyme has a pivotal role in the remodelling of large LDL into small LDL through its action on LDL-TAG. Hence, LDL subclasses were shown to redistribute at about a TAG threshold of 1-5mmol/l, a finding concordant with the influence of TAG-lowering drugs (Superko & Gauss, 1992;Caslake et al 1993). This relatively low TAG value has been ascribed clinical significance in NIDDM (Lahdenpera et al 1996) and in the expression of small, dense LDL in an ALP (Austin et al 1990), suggesting that current action limits for intervention may be too high.…”
Section: Plasma Triacylglycerols and Ldl Subclassessupporting
confidence: 64%
“…10 Fibrate treatment results in a reduction of the LDL fraction of atherogenic small, dense particles with an equivalent increase in the intermediate subfraction. [11][12][13] Within the triglyceride-rich apolipoprotein (apo) B-containing lipoproteins, fibrates efficiently reduce the apoC-III-containing particles, 14,15 which are markers for increased risk for atherogenesis. 16 The increased HDL concentrations after fibrates are generally reflected by increased plasma levels of apoA-I and apoA-II, 14,15 a change that is associated with an increase in lipoprotein (Lp) A-I:A-II, and a decrease in LpA-I concentrations in patients treated with fenofibrate.…”
Section: Pharmacological Action Of Fibratesmentioning
confidence: 99%